(untitled) (Research, Society and Development, 2021)
The analysis of the participation of dentists in the scientific subfield of collective Health (SC) was carried out through a cross-sectional study to characterize the profile of the professors of the postgraduate programs in collective Health (PPGSC) with graduation in Dentistry and its relations with the SC space. The Lattes curricula of the 141 professors who participated in the CAPES evaluation 2017 were identified and collected. The referential of Bourdieu’s theory of practices was used. The variables analyzed: PG program to which it belongs; Area and theme of doctoral thesis and master’s dissertation; First and second practice areas; Occupations outside the university; First line of research; and 5 main published works; and the volume of scientific and bureaucratic capital. Professors with a degree in dentistry were linked to 52 PPGSC, from 39 different institutions, and 66% from federal public institutions. A predominance of the area of activity in SC was observed. Most professors were female, but positions of greater notoriety in the scientific field and more qualified publications were related to men. The significant relationship of these professors with the dental field reveals their strong influence on professional identity, establishing a fine line between these two scientific fields.